2021
DOI: 10.1111/jvim.16113
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized dexamethasone sodium phosphate in the treatment of horses with severe asthma

Abstract: Background: A study reported low systemic availability of injectable dexamethasone nebulized to healthy horses using the Flexineb mask. When used in horses with severe asthma and a different nebulizer, lack of efficacy and cortisol suppression were observed.Hypothesis: Nebulized dexamethasone is as effective as PO administration for the treatment of severe asthma in horses.Animals: Twelve horses with severe asthma from a research herd.Methods: Randomized clinical trial. Horses were divided into 2 groups and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…7 Studies in horses with severe asthma report a rapid significant decrease in serum cortisol concentration after 3 (reduction: 52.4 nmol/L [converted from 1.9 μg/dL]) 2 and 7 (reduction: 57.9 nmol/L [converted from 2.1 μg/dL] 2 ; 44.7 nmol/L 3 ) days of nebulized administration of dexamethasone (5 mg q24h). Consistent with these studies, 2,3 we observed a significant decrease in blood endogenous cortisol at Day 7 and Day 14 of 62 and 59 nmol/L respectively, and as expected, the magnitude of cortisol suppression was greater than that observed at the lower dose rate (5 mg).…”
Section: Saline Treatment Group Vssupporting
confidence: 91%
See 3 more Smart Citations
“…7 Studies in horses with severe asthma report a rapid significant decrease in serum cortisol concentration after 3 (reduction: 52.4 nmol/L [converted from 1.9 μg/dL]) 2 and 7 (reduction: 57.9 nmol/L [converted from 2.1 μg/dL] 2 ; 44.7 nmol/L 3 ) days of nebulized administration of dexamethasone (5 mg q24h). Consistent with these studies, 2,3 we observed a significant decrease in blood endogenous cortisol at Day 7 and Day 14 of 62 and 59 nmol/L respectively, and as expected, the magnitude of cortisol suppression was greater than that observed at the lower dose rate (5 mg).…”
Section: Saline Treatment Group Vssupporting
confidence: 91%
“…The 15 mg daily dosage of dexamethasone administered via nebulization used in the present study was greater than described in 2 trials of horses with severe asthma trials 2,3 . The reason for this was the lack of improvement in lung mechanics reported with a dosage of 5 mg dexamethasone sodium phosphate nebulized once daily in horses with severe asthma in both previous studies 2,3 .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…While this may have contributed to a dampened maximal urine lidocaine concentration in the 1–3 h post-nebulization, this is considered unlikely to have changed the duration that lidocaine and MEGX were detectable in urine, as xylazine requires 30–60 min to cause a significant increase in the rate of urine production ( 39 ), and urinary catheterization was completed within 10 min of xylazine administration. As drug deposition in the distal airways is impeded by modifications in breathing pattern, cough, bronchoconstriction, and airway secretions such as mucus often present in EA ( 40 ), investigation into drug delivery in clinically affected animals remains essential to ensure that therapeutic concentrations are achieved. However, the peak serum concentrations achieved in healthy horses here indicate that nebulized lidocaine dosages in excess of 1 mg/kg may be safely considered, if needed to achieve clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%